Role of the Polyadenylate Segment in the Translation of Globin Messenger RNA in Xenopus Oocytes - Huez, G. (1974)
The translations of native messenger RNA for rabbit globin and that of poly(A)-free globin messenger RNA have been compared after injection into Xenopus oocytes. The initial rate of translation of poly(A)-free mRNA is close to that found with intact mRNA. However, at longer incubation periods, the rate of globin synthesis with poly(A)-free mRNA is considerably lower than with native mRNA. Similar differences in the template activity of the two mRNA preparations were found with a cell-free extract of Krebs II ascites tumor. It is concluded that the presence of the 3′ poly(A)-rich sequence in mRNA is required to ensure high functional stability.